Cross-Border Insolvency Theories and the Public Policy Exception - Jayshree, V; Biswal, Mamata (NLUJ, 2024)
This paper critically examines Article 6 of the UNCITRAL Model Law on Cross-Border Insolvency, 1997, prominently known as “the public policy exception”. It highlights the tension between the theories of Territorialism and Modified-Universalism in interpreting the “manifestly contrary clause” contained within this exception, reflecting a broader tension between the desire for international legal harmonization and the preservation of national legal autonomy. By exploring the diverse enactment and interpretation of Article 6 among Model Law, 1997 adoptee countries, this article reveals that narrow interpretation aligns with Modified-Universalism, while broad interpretation corresponds to Territorialism. Case analysis indicates Territorialism as an antithesis to the harmonization efforts sought by the Model Law, 1997. Additionally, it is noted that some Asian Countries have enacted Article 6 in a manner that allows wide interpretation, which is against the guidelines of Model Law, 1997. This article concludes with a compelling call for greater international cooperation, recommending uniform enactment and interpretation of Article 6 to enhance global legal consistency in cross-border insolvency cases.
Keywords: Public Policy Exception; Modified-Universalism; Manifestly Contrary Clause; Cross-Border Insolvency; Article 6